2017
DOI: 10.1186/s40623-017-0748-6
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy particle experiments–electron analyzer (LEPe) onboard the Arase spacecraft

Abstract: In this report, we describe the low-energy electron instrument LEPe (low-energy particle experiments-electron analyzer) onboard the Arase (ERG) spacecraft. The instrument measures a three-dimensional distribution function of electrons with energies of ∼ 19 eV-19 keV. Electrons in this energy range dominate in the inner magnetosphere, and measurement of such electrons is important in terms of understanding the magnetospheric dynamics and waveparticle interaction. The instrument employs a toroidal tophat electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 10 publications
(8 reference statements)
0
55
0
Order By: Relevance
“…Therefore, the azimuthal channels 0 and/or 15 of the MEP-i are intermittently irradiated with the solar EUV flux. The FOV of the MEP-i is partially blocked by the adjacent particle instrument (LEP-e, Kazama et al 2017) on the same panel, the solar array paddle yokes, and wire-antenna (PWE, Kasahara et al 2017). The largest FOV blocking, caused by the yokes, is below 10°.…”
Section: Instrumentationmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, the azimuthal channels 0 and/or 15 of the MEP-i are intermittently irradiated with the solar EUV flux. The FOV of the MEP-i is partially blocked by the adjacent particle instrument (LEP-e, Kazama et al 2017) on the same panel, the solar array paddle yokes, and wire-antenna (PWE, Kasahara et al 2017). The largest FOV blocking, caused by the yokes, is below 10°.…”
Section: Instrumentationmentioning
confidence: 95%
“…It holds a much larger analyzer constant compared to the conventional top-hat spherical (Carlson et al 1982) and toroidal (Young et al 1988) ESAs. These conventional ESAs are frequently dedicated to measurements of lowenergy (≤ ~ 30 keV/q) particles and are utilized for ERG mission (Asamura et al in preparation;Kazama et al 2017). Although a spherical ESA for the Juno mission covers an energy range of 0.1-100 keV by using the electric field up to 4 kV/mm (McComas et al 2013), the cusp-type ESA achieves the 180-keV ion measurement with the electric field of 2 kV/mm.…”
Section: Cusp-type Esa Energy/charge Analysesmentioning
confidence: 99%
“…The appearance and enhancement of radio and plasma waves such as UHR, ESCH, and NTC waves in a frequency range covered by the HFA in geomagnetically disturbed conditions suggest that there are energetic electrons that may be a free energy source of the plasma waves in the storm-time magnetosphere. It is therefore important to perform a detailed comparison between HFA data and the energetic electron data obtained by Arase/LEP-e (Low-Energy Particle Experiments-Electron Analyzer) (Kazama et al 2017) and Arase/MEP-e (Medium-Energy Particle Experiments-Electron Analyzer) (Kasahara et al 2018a). An example of the spectrograms obtained in PP-1 and EB modes is shown in Fig.…”
Section: Radio and Plasma Waves During Geomagnetically Quiet And Distmentioning
confidence: 99%
“…On the other hand, Kalaee and Katoh (2016) reported that R-X mode KC are also observed by the Akebono satellite, suggesting that R-X mode waves can be generated by nonlinear interactions between Z-mode waves and energetic electrons based on simulations. Further discussion will be enabled by HFA EE-LR mode data and energetic electron data around the plasmapause obtained by Arase/LEP-e (Kazama et al 2017) and MEP-e (Kasahara et al 2018a). …”
Section: Radio and Plasma Waves During Geomagnetically Quiet And Distmentioning
confidence: 99%
“…The generated data packets are compressed and sent to the data recorder operated by the satellite bus system through a telemetry/ command interface based on SpaceWire (Takashima et al 2018). In addition to LEPi, the CPU board controls the low-energy particle experiments-electron analyzer (LEPe) (Kazama et al 2017) via a command/data handling interface (SpaceWire). Onboard processing of LEPe raw data also occurs on the CPU board.…”
Section: Overviewmentioning
confidence: 99%